The Choosing People: Interpreting the Puzzling Politics of American Jewry. Issue 1 (28th October 2014) - Wald, Kenneth D.
Abstract: The political liberalism of American Jews is puzzling because it contradicts the assumption that economic self-interest drives political behavior. Attempts to solve this puzzle with "Judaic" explanations compound the problem by offering theories that are static and universal while American Jewish political behavior is dynamic and situational. Using both historical and behavioral data, I argue that the solution to these puzzles is found in the overriding concern of American Jews with maintaining their equal citizenship in a society with a classic liberal regime of religion and state. This situational model also helps integrate work on Jewish political studies with theories and concepts commonly used by political scientists to explain mass political behavior.